2023
DOI: 10.1186/s12875-023-01981-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies to increase smoking cessation treatment provision in primary care: a systematic review of observational studies

Abstract: Background Internationally, there is an ‘evidence-practice gap’ in the rate healthcare professionals assess tobacco use and offer cessation support in clinical practice, including primary care. Evidence is needed for implementation strategies enacted in the ‘real-world’. Aim: To identify implementation strategies aiming to increase smoking cessation treatment provision in primary care, their effectiveness, cost-effectiveness and any perceived facilitators and barriers for effectiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Regarding barriers and facilitators (RQ3), the most frequently reported barriers were "available resources," "knowledge and beliefs about the intervention," and "patient needs and resources" in clinical settings. These barriers were consistent with previous studies that reported time limitations, low priority, lack of knowledge among healthcare professionals, and providers' perception that patients were not interested in smoking cessation as barriers to primary care [103,104], including a scoping review in South Asian regions [105]. The most frequently reported facilitator was "relative priority."…”
Section: Discussionsupporting
confidence: 87%
“…Regarding barriers and facilitators (RQ3), the most frequently reported barriers were "available resources," "knowledge and beliefs about the intervention," and "patient needs and resources" in clinical settings. These barriers were consistent with previous studies that reported time limitations, low priority, lack of knowledge among healthcare professionals, and providers' perception that patients were not interested in smoking cessation as barriers to primary care [103,104], including a scoping review in South Asian regions [105]. The most frequently reported facilitator was "relative priority."…”
Section: Discussionsupporting
confidence: 87%
“…We know from the implementation research field that facilitation and effective implementation strategies are often needed to succeed with implementation long-term ( 33 , 34 ). Several strategies can be found that support health care practitioners to perform smoking cessation activities and cue their behavior in the “right” direction.…”
Section: Discussionmentioning
confidence: 99%
“…To provide sound advice on smoking cessation, HCPs must be knowledgeable and possess the right attitude, which is crucial to giving meaningful advice. In a recent systematic review, Tildy et al ( 2023 ) found that a lack of knowledge among health providers and inadequate messaging about cessation support options are significant barriers to successful smoking cessation interventions (Tildy et al 2023 ). This finding assesses HCPs’ knowledge, attitudes and practices (KAP) on smoking cessation interventions.…”
Section: Introductionmentioning
confidence: 99%